The internal factors affecting the successful of ISO9001 quality system implementation in Siegwerk Malaysia Sdn Bhd / Nurul Fatihah Hasmuni - Hasmuni, Nurul Fatihah (2013)
This research studies is about the internal factors which is including employee and the company’s environment that affecting the successful of ISO9001 quality system implementation in Siegwerk Malaysia Sdn Bhd. The aim of this study is to identify the significant correlation relationship between the four factors which is commitment, following documented working procedure, awareness and working environment with the succesfull of ISO 9001 implementation in Siegwerk (M). The successful implemtation of ISO9001 quality system will give benefit to the company in term of financial profit efficient work quality and enhance customer trust. Data is collected through questionnaire distributed to 60 respondents in Siegwerk Malaysia. The survey method employed was quantitive data to describe the respondent’s profile in Section A of the questionnaire such as gender, age, length of service, and education level. Reliability test was used to to fin out if the questionnaire was reliable or not. The correlation test was used investigate relationship of dependent variable and independent variable to satisfied the objective of the research. This study is said to be beneficial to the company especially as they are currently facing internal problem in maintaining ISO9001 quality system implementation. It will help them to gain understand the employees feedback on the implementation of ISO9001 quality system and consider the recommendations that having been discussed.